Penerapan Sistem Informasi Profil Desa Berbasis Web Di Desa Situnggaling - Jijon R Sagala; Penda Sudarto Hasugian; Sulindawaty Sulindawaty (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Technology makes it easy to help every human activity in conveying information both government agencies, private agencies and so on, including in the field of village government. At this time the Situnggaling Village Government still uses manual systems such as banners, letters, pamphlets and billboards in providing information which in the end the community cannot obtain the information they need at any time, so a lot of information is unknown. The purpose of this service is to design and implement a web-based Village profile information system in Situnggaling Village. This web-based village profile information system has several features, namely village profiles, population data and related information in the village. The target in the implementation of STMIK Pelita Nusantara Excellence Service is how to develop a web-based village profile information system in Situnggaling village, by facilitating village officials to be more skilled in using information systems and publicizing the potential of the village, as well as conducting training so that village officials are able to manage proper administration. even better with digital based. Village officials received a training module for the implementation of a web-based village profile information system application in Situnggaling village.